How to speak Dragonese - Cowell, Cressida (How to train your dragon ;, 2006)
Recounts the further escapades of Hiccup Horrendous Haddock the Third as he continues his Viking training during which he escapes from a boatload of Roman soldiers and searches for his kidnapped dragon.